Dispatches from Palestine : the rise and fall of the Oslo peace process - Usher, Graham, 1958- (Middle East issues., 1999)
'Usher ... does the best foreign on-the-spot reporting from Palestine.' Edward Said, London Review of Books 'The reader vicariously experiences what will become great moments of popular oral history that official historians will forget in the great scheme of things.' Middle East International.